Ekspansi Kompeni Hingga Sanad Kiai-Santri: Sejarah Islamisasi Ujung Timur Pulau Jawa Abad XVIIâXX - Subekti, Arif (SHAHIH: Journal of Islamicate Multidisciplinary, 2017)
This study aims to examine the history of Islamization missionary in Banyuwangi, Eastern Java from 17th century to 20th century. This study identifies the agent of Islamization, motive, a model of dawah, as well as narrating the attitude and form of acceptance of the Banyuwangi communities. This study deals with a historical approach to gain the answer to the research questions and uses the primary and secondary data such as archives, oral sources, and some relevant references. The conclusions of this study are; first, the Eastern Java was the last section region of Islamization in Java; second, the collaboration of colonial power and the Kingdom of Mataram played important role in Islamization process; third, the depopulation has direct relation toward Islamization and domination of Java and Madura ethnicity; fourth, the chain of Islamic scientific and teacher-students relationships describe the teacher-student lines of Islamization.